Pengaruh Penambahan Bakteri Acetobacter Xylinum Terhadap Kualitas Produk Ecoenzym - Nurul Fathiris Salma; Naniek Ratni (Yayasan Literasi Sains Indonesia, 2022)
According to SIPSN data, the total waste in 2021 was 41,230,997.98 tons / year and it was 45.9% as the highest which came from household activities. Vegetable and fruit waste can be used as a more useful product such as being used as an ingredient for making Ecoenzym solution. Ecoenzyme is the result of fermentation of organic kitchen waste such as vegetable and fruit pulp with a mixture of sugar and water. The presence of sugar mixture in the ecoenzyme fermentation process has an important role as a source of nutrition for Acetobacter Xylinum bacteria. The addition of Acetobacter Xylinum starter in this experiment is to find out how the addition of Acetobacter Xylinum starter affects the quality of ecoenzyme products and the duration of their manufacture. In this experiment, the variables set were papaya peel used, the dose of making ecoenzyme, namely (3 fruit peels: 1 palm sugar: 10 water) and the starter used was the Acetobacter Xylinum starter. The variation made in this observation are the variation in the number of starters, which are 5%; 10%; 15%; 20%, the initial pH of fermentations are 4; 5; 6 and will be fermented for 10 days; 12 days; 14 days; 16 days; 18 days; and 90 days. Based on the observations of the final ecoenzym results, the content of acetic acid, Nitrate (NO3), Color, Final pH, and Water Content in the ecoenzyme filtrate is respectively (number of starters; Initial pH; fermentation time) : (15%; 4; 90 days), (20%; 4; 90 days), (10%; 5; 90 days), (10%; 5; 90 days), (5%; 6; 18 days). The conclusion of this observation is that the addition of Acetobacter Xylinum starter tends to produce better ecoenzyme products, but the duration of manufacture has not been able to be shortened.